African politics in comparative perspective - Hydén, Göran, 1938- (Cambridge University Press, 2006)
By reviewing fifty rears of research on politics in Africa, this volume offers the most comprehensive text on this subject that has been written in many years. It also shows how research on African politics relates to the study of politics in other regions of the world.